2017
DOI: 10.5535/arm.2017.41.6.1019
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Clinical Characteristics Between Patients With Different Causes of Vocal Cord Immobility

Abstract: ObjectiveTo analyze the clinical characteristics between neurogenic and non-neurogenic cause of vocal cord immobility (VCI).MethodsThe researchers retrospectively reviewed clinical data of patients who underwent laryngeal electromyography (LEMG). LEMG was performed in the bilateral cricothyroid and thyroarytenoid muscles. A total of 137 patients were enrolled from 2011 to 2016, and they were assigned to either the neurogenic or non-neurogenic VCI group, according to the LEMG results. The clinical characteristi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 35 publications
1
5
0
Order By: Relevance
“…In another retrospective study in 137 patients, L-EMG results showed that SLN, recurrent laryngeal nerve or both were damaged in 94 patients, while 43 patients had normal findings. Twenty five percent of the neurogenic involvement has been reported to be idiopathic, while others have been reported after the treatment of thyroid, parathyroid, lung and pancreatic malignant tumors (9). In our study, we found that 12 of 14 patients with functional disorder and 4 of 10 patients with organic disorder had neurogenic involvement in L-EMG.…”
Section: Discussionsupporting
confidence: 50%
“…In another retrospective study in 137 patients, L-EMG results showed that SLN, recurrent laryngeal nerve or both were damaged in 94 patients, while 43 patients had normal findings. Twenty five percent of the neurogenic involvement has been reported to be idiopathic, while others have been reported after the treatment of thyroid, parathyroid, lung and pancreatic malignant tumors (9). In our study, we found that 12 of 14 patients with functional disorder and 4 of 10 patients with organic disorder had neurogenic involvement in L-EMG.…”
Section: Discussionsupporting
confidence: 50%
“…To identify the neurogenic cause of laryngeal dysfunction and the severity of nerve injury, we performed pre‐treatment laryngeal electromyography. 9 Patients who refused laryngeal electromyography or were at a high risk of bleeding (platelet < 50 000 or INR > 3.0) or infection (absolute neutrophil count < 500) were not tested but were not excluded from the study. The result of the electromyography was used to help with patient counseling.…”
Section: Methodsmentioning
confidence: 99%
“…Another possible reason could be an infection of the recurrent nerve itself ( 10 , 19 ). We could exclude this in our patient because the intraoperative electromyography of the vocal muscle on both sides showed normal action potentials ( 20 ).…”
Section: Discussionmentioning
confidence: 97%